2017
DOI: 10.5101/nbe.v9i3.p249-274
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of the Effect of Rigid and Dynamic Posterior Attachment Systems on Stress Reduction in Cortical and Spongy Bones of the Lumbar Segments L4-L5

Abstract: Posterior instrumentation is a common fixation method used in the treatment of spinal diseases. However, the role of different models of fixation system in improving fixation stability in these fractures has not been established. Comparative investigation between posterior rigid fixation (pedicle screw) and four models of posterior dynamic fixation (B Dyne, Elaspine, Bioflex, Coflex rivet) may elucidate the efficacy of each design. The purpose of this study was to investigate the biomechanical differences betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
(74 reference statements)
0
0
0
Order By: Relevance
“…On the other hand, the bicortical fixation always engage with both the near and far cortical bones [19]. Rectangular shape of screw thread was used in this study as it shown to give a uniform surface stress distribution [26]- [27]. The 2D model was constructed by 3 mm homogeneous cortical bone layers at upper and bottom of cancellous bone and 20 mm cancellous bone region as listed in Table 2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the bicortical fixation always engage with both the near and far cortical bones [19]. Rectangular shape of screw thread was used in this study as it shown to give a uniform surface stress distribution [26]- [27]. The 2D model was constructed by 3 mm homogeneous cortical bone layers at upper and bottom of cancellous bone and 20 mm cancellous bone region as listed in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…These situations demonstrate that at the bone-implant interaction, it experienced stress shielding response where normal mechanical stress of bones reduced, resulting in bone loss in the region of implants [26]. Even though loosening of the screw has been well reported in the literature, there are still lacking regarding the bone-screw interaction involving the reduction of stress shielding and bone remodelling of fully threaded cortical screw as most of previous study focused on partial thread screw and dental implant.…”
Section: Introductionmentioning
confidence: 95%